DNA Mismatch Repair Proteins and BRAF V600E Detection by Immunohistochemistry in Colorectal Cancer Demonstrates Concordance with Next Generation Sequencing - Joel Yambert; Leigh A. Henricksen; June Clements; Andrew Hannon; Alyssa Jordan; Shalini Singh; Katerina Dvorak; Colin C. Pritchard; Eric Q. Konnick (MDPI AG, 2022)
Background and Aims: Multiple laboratory methods are used to screen patients with colorectal cancer (CRC) for mismatch repair (MMR) protein deficiency to identify possible Lynch syndrome patients. The goal of this study was to compare the agreement between ready-to-use immunohistochemistry (IHC) assays for MLH-1, PMS-2, MSH-2, MSH-6, and mutated BRAF at V600E and molecular methods in CRC cases. The inclusion of the BRAF V600E mutation testing is important for the identification of patients with sporadic CRC, as the BRAF V600E mutation is very rarely observed in patients with Lynch syndrome tumors. Methods: CRC cases were analyzed by ColoSeqTM tumor sequencing assay and VENTANA MMR IHC Panel that included anti-MLH1, anti-PMS2, anti-MSH2, anti-MSH6, and anti-BRAF V600E antibodies. Additionally, CRC cases with MLH1 IHC loss were evaluated for MLH1 promoter hypermethylation. Results: One hundred and eighteen cases were analyzed. The overall percent agreement (OPA) for each evaluated marker status compared to next-generation sequencing (NGS) exceeded 96%. Twenty-three cases were positive for the BRAF V600E mutation by IHC and NGS, and twenty cases showed loss of MLH1 protein and were positive for MLH1 hypermethylation. Samples with loss of MMR protein expression by IHC demonstrated genetic and/or epigenetic alterations that were consistent with the observed protein expression patterns. Conclusions: The results of this study indicate that ready-to-use IHC assays can correctly identify the loss of MMR proteins and the presence of mutated BRAF V600E protein, supporting the utility of the VENTANA MMR IHC Panel as an aid to stratify patients with sporadic CRC vs. potential Lynch syndrome.